2018
DOI: 10.1002/jum.14818
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Printed Cardiac Models for Focused Cardiac Ultrasound Instruction

Abstract: Background Focused cardiac ultrasonography (FCU) is an increasingly integral component of routine medical training and practice. While various instructional methods have been described, few attempts have been made to incorporate a physical 3‐dimensional (3D) instructional aid. Objective The aim of this study was to determine if a 3D printed heart model workshop for FCU instruction leads to equivalent structure recognition and scanning ability compared to traditional didactic FCU instruction. Intervention Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
5
1
1
Order By: Relevance
“…McKenna et al described a 3D printed trainer for the in vitro training of TEE; here, the focus was the phantom model and not the cardiac model itself [ 12 ]. Ochoa et al also used 3D models in TTE teaching and could not detect a significant effect on learning efficiency, which somehow is contradictory to our results but is probably secondary to the smaller group size and the different setup of their study [ 14 ]. This underlines the need for larger-scale, in depth studies on the role of three-dimensional models in evidence-based medical- and surgical education.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…McKenna et al described a 3D printed trainer for the in vitro training of TEE; here, the focus was the phantom model and not the cardiac model itself [ 12 ]. Ochoa et al also used 3D models in TTE teaching and could not detect a significant effect on learning efficiency, which somehow is contradictory to our results but is probably secondary to the smaller group size and the different setup of their study [ 14 ]. This underlines the need for larger-scale, in depth studies on the role of three-dimensional models in evidence-based medical- and surgical education.…”
Section: Discussioncontrasting
confidence: 99%
“…It therefore appears plausible to transfer the concept to echocardiographic training. Surely, 3D Models have been used earlier for TTE-teaching, but the didactic effects are poorly studied: in the only scientific evaluation we are aware of, no didactic advantages have been demonstrated for the 3D-model use [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 9 identified randomized controlled trials, 7 were conducted in the field of education and training. 6 , 7 , 8 , 9 , 10 , 11 , 12 Results were inconsistent in terms of knowledge gain for students and trainees compared with nonpersonalized models or standard lectures. The only randomized controlled trial investigating the use of 3DPSPs in cardiovascular intervention demonstrated a reduction of intervention time during left atrial appendage occlusion.…”
Section: Resultsmentioning
confidence: 98%
“… 63 However, compared with virtual 3D models, 3DPSPs additionally provide haptic feedback and allow training in practical steps, as demonstrated in several studies. 6 , 7 , 8 , 9 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…S. Ochoa и соавт. применяли 3D-модели сердца при обучении ЭхоКГ для улучшения понимания обучаемыми плоскостей сканирования [27].…”
unclassified